Efforts to Improve Student Activity and Learning Achievement in Mathematics Learning Using Game Methods at Madrasah Ibtidaiyah Pasirmuncang - Wahyudin, Hendi (Journal of Indonesian Primary School, 2025)
The results of observations in the classroom during mathematics learning, grade VI students tend to be passive and students' mathematics learning activities are very lacking. For mathematics lessons, the average score obtained by grade VI students on the material of reading and writing integers which was the material before this research was conducted was 47.73 and the percentage of students who achieved the learning completion standard was 30.43%. This value is very far from the percentage of students who achieved the teaching and learning completion standard (SKBM) set at Madrasah Ibtidaiyah Pasirmuncang, Sagaranten District, which is 70%. This classroom action research (PTK) was carried out using the game method in an effort to improve the activity and achievement of mathematics learning of grade VI students at Madrasah Ibtidaiyah Pasirmuncang, Sagaranten District. The research was carried out in two cycles, each consisting of two meetings through the following stages: planning, action, observation and reflection. Data collection techniques were carried out through observation sheets for each meeting by observers to see data on learning activities, while data on learning outcomes were obtained through daily test scores and students' mathematics learning achievements in cycle 1 and cycle 2. The results obtained from Classroom Action Research (CAR) through the game method model showed an increase in student activity results, especially in activities to prepare places, materials and tools by 51.65%, activities to express ideas by 62.76% and for activities to read game rules and books experienced by 71.07%. Based on data on students' mathematics learning achievements, the average class score in cycle I was 64.26, increasing to 71.51 in cycle II. The percentage of students who achieved the completion standard also increased in cycle I by 78.88% (Good Category), increasing to 90% (Excellent Category) in cycle II.